Verbraucherleitbilder : Interdisziplinäre und europäische Perspektiven - Klinck, Fabian; Riesenhuber, Karl (Schriften zum Europäischen und Internationalen Privat-, Bank- und Wirtschaftsrecht ;, 2015)
Politicians, legislators, academics, and consumer lawyers all base their regulatory interventions on a particular concept of the consumer. These proceedings of the General Concept of the Consumer conference aim to provide an up-to-date inventory of interdisciplinary and comparative foundations and to stimulate further dialogue on consumer models, both within and between disciplines.